Development of agricultural technology for different user categories: Some ILCA experiences - Whalen, I.T. (Rockefeller Foundation, 1985)
Reviews ILCA's mandate, position, and organizational structure; discusses ILCA's experience with identification of user categories, their needs and potential; examines studies on single-ox plow in Ethiopia; and outlines opportunities for strengthening the users' perspective.